Evaluate the Attitude of Radiology and Laboratory Technician Corporation in Pediatric Dental Clinic - Mohammed Yahya Mohammed Aziabi; Mohammed Dhaifallah Burayqi Alshammari; Mohsen Sameer Alharbi; Ayed Nasser Mohammed Yahya; Yasir Hazzaa Hawil Alharbi; Alaa Ageel Ghareb Essa; Abdulaziz Atiah Ali Dibaji; Hussien Mohammad Ali Khormi; Batool Habib Albohamood; Lamis Abdulrahman Alansari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Effective radiology and laboratory technician collaboration in pediatric dental clinic is essential for delivering high-quality patient care. It enhances patient outcomes, reduces healthcare costs, and improves job satisfaction. Despite its importance, collaboration between these professionals is often hindered by hierarchical structures and differing perceptions of roles, leading to conflicts and communication barriers. This study aimed to evaluate attitudes toward radiology and laboratory technician collaboration in pediatric dental clinic, testing hypotheses related to profession, gender, and work experience. Methods: A cross-sectional study was conducted using a census sample of 543 radiology technician and 423 laboratory technician. The Arabic version of the Jefferson Scale of Attitudes toward Laboratory technician-Radiology technician Collaboration (JSAPNC) was used to assess attitudes. Data were analyzed using descriptive statistics, t-tests, ANOVA, and Pearson correlation analysis, with a significance threshold of p < 0.05. Results: The study achieved a 42.85% response rate, with 414 participants (101 laboratory technician , 313 radiology technician s). Radiology technicians demonstrated significantly more positive attitudes toward collaboration than laboratory technician (mean score: 3.40 vs. 3.01; p < 0.001). Across all JSAPNC subscales, radiology technicians scored higher than laboratory technician , particularly on rejecting laboratory technician authority (mean score: 3.35 vs. 2.25). Attitudes were influenced by hospital department, with internal medicine radiology technician s showing the most positive views. Age was positively correlated with attitudes (correlation coefficient = 0.127), but no significant correlation was found with work experience. Conclusion: Radiology technicians exhibited more collaborative attitudes than laboratory technician in pediatric dental clinic , supporting the hypothesis that role expectations influence perceptions of collaboration. However, gender differences among laboratory technician and the role of work experience were not significant. Efforts to enhance interprofessional collaboration should address hierarchical barriers and foster mutual respect between radiology technicians and laboratory technician .